Analisis Kelayakan Usaha Budidaya Jamur Tiram di Kota Bengkulu - Wulandari, Dwi; Mulyasari, Gita; Reswita, Reswita (Musamus University, 2023)
The purpose of this study was to analyze the cost, revenue, income and feasibility of oyster mushroom cultivation in Bengkulu City. The analytical tools used are descriptive analysis, income analysis, and business efficiency. The results showed that the average total costs incurred in 4 months of production amounted to IDR 12,743,758/MT or IDR 249,877/MT/m² which consists of fixed costs (tool depreciation costs and kumbung depreciation) and variable costs (baglog production, baglog purchases, labor wages, plastic packaging and firewood costs), the average revenue obtained is IDR 19,264. 500/MT or IDR 377,500/MT/m². The average income earned is IDR 6,520,742/MT or IDR 127,857/MT/m². Oyster mushroom cultivation in Bengkulu City is feasible with an R/C value of 1.5.